2017
DOI: 10.1021/jacs.7b03507
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Morphological Dual Modulation of Cobalt Carbonate Hydroxides by Mn Doping toward Highly Efficient and Stable Bifunctional Electrocatalysts for Overall Water Splitting

Abstract: Developing bifunctional efficient and durable non-noble electrocatalysts for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) is highly desirable and challenging for overall water splitting. Herein, Co-Mn carbonate hydroxide (CoMnCH) nanosheet arrays with controllable morphology and composition were developed on nickel foam (NF) as such a bifunctional electrocatalyst. It is discovered that Mn doping in CoCH can simultaneously modulate the nanosheet morphology to significantly increase the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
517
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 770 publications
(543 citation statements)
references
References 76 publications
22
517
0
Order By: Relevance
“…[25] Thev ariation in the position of the pre-peaks can be explained by the different electron environment around the metal centers ( Figure 2). [27] This clearly shows the superiority of the templated approach to obtain high current density at low overpotential. Only 240 mV overpotential is required for t-Co II -Co III to reach the anodic current density of 10 mA cm À2 .Importantly,the water oxidation current density obtained for t-Co II -Co III is far better than the template-free catalyst f-Co II -Co III under similar reaction conditions.Moreover,the templated catalyst outperforms the water oxidation activity of the noble metal catalyst RuO 2 in alkaline medium and many other carbon cloth supported first-row transition-metal catalysts reported previously (Supporting Information, Table S2).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…[25] Thev ariation in the position of the pre-peaks can be explained by the different electron environment around the metal centers ( Figure 2). [27] This clearly shows the superiority of the templated approach to obtain high current density at low overpotential. Only 240 mV overpotential is required for t-Co II -Co III to reach the anodic current density of 10 mA cm À2 .Importantly,the water oxidation current density obtained for t-Co II -Co III is far better than the template-free catalyst f-Co II -Co III under similar reaction conditions.Moreover,the templated catalyst outperforms the water oxidation activity of the noble metal catalyst RuO 2 in alkaline medium and many other carbon cloth supported first-row transition-metal catalysts reported previously (Supporting Information, Table S2).…”
mentioning
confidence: 84%
“…As the t-Co II -Co III is transformed into al ayered hydroxide structure during OER (see later), we have compared the activity with reported layered double hydroxide catalysts and better performance of our catalyst is observed (Supporting Information, Table S2). [27] This clearly shows the superiority of the templated approach to obtain high current density at low overpotential. Thea ctivity of the templated PBAa lso surpasses the PBAd erived electrocatalysts like phosphides,s ulfides,n anoalloys,o ro xides prepared by high temperature multistep method (Supporting Information, Table S2).…”
mentioning
confidence: 84%
“…Electrocatalytic water splitting into hydrogen and oxygen provides a prospective and competitive technology to generate sustainable and renewable energy sources. [1][2][3] Nevertheless, the high overpotentials of both half-cell reaction, i. e., hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), heavily restrict a real application of overall water splitting. [4] Up to now, the benchmark catalyst for OER is IrO 2 or RuO 2 , while that for HER is Pt/C due to their high activities.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this goal, building well-aligned arrays of active components on three-dimensional (3D) conductive current collectors seems to be a useful approach, since it can expose large specific surface areas to allow easy spread of ions and therefore increases intrinsic activity of the active sites toward catalysis applications. [36][37][38][39][40] For instance, Qiao and co-workers [41] boosted the OER activity of Co 3 O 4 by directly grown porous Co 3 O 4 -based nanowire arrays on Cu foil. Li et al [42] also fabricated interconnected Co 3 Few reports demonstrated the design of maximizing the relative content of active Co 3 + species of to get benefit in the OER process.…”
Section: Introductionmentioning
confidence: 99%